Data Concealment Technique in Background Segmentation of Color Image Based Secure Data Transmission System - Al-Phalahi, Khamael A (Al-Nahrain Journal of Science, 2011)
Image based steganography is the most popular method for data concealment. In this paper a new approach for data concealment in background segments of color image called JSEG, (J-image segmentation) is presented. A criterion to local windows in the class-map results of the “J-image”, is applied in which high and low values correspond to possible region boundaries and region centers, respectively then a region growing method is used to segment the color image to regions based on the multi-scale J-images. The adopted system combines the effect of two methods to enhance the security of the data. System encrypts the data with a crypto algorithm and then embeds the encrypted text in a segmentation background of color image file and then merged background with other regions segmentation. The (increase in PSNR) leads to provide high secret communications, so the attacker cannot notices the difference between the stego-image and the original cover.